Comparative Metabolomics Reveals Key Pathways Associated With the Synergistic Killing of Colistin and Sulbactam Combination Against Multidrug-Resistant Acinetobacter baumannii - Han, Mei-Ling; Liu, Xiaofen; Velkov, Tony; Lin, Yu-Wei; Zhu, Yan; Creek, Darren J.; Barlow, Christopher K.; Yu, Heidi H.; Zhou, Zhihui; Zhang, Jing; Li, Jian (Frontiers in Pharmacology, 2019)
Background: Polymyxins are a last-line class of antibiotics against multidrug-resistant Acinetobacter baumannii. However, polymyxin resistance can emerge with monotherapy, highlighting the need for synergistic combination therapies. Polymyxins in combination with -lactams have shown remarkable synergy against MDR A. baumannii. Methods: LC-MS based metabolomics was conducted to investigate the metabolic perturbations in an A. baumannii clinical isolate, AB090342, in response to colistin (1 mg/L), sulbactam (128 mg/L), and their combination at 1, 4, and 24 h. Metabolomics data were analyzed using univariate and multivariate statistics, and metabolites showing 2-fold changes were subjected to pathway analysis. Results: The synergistic activity of colistin-sulbactam combination was initially driven by colistin through perturbation of fatty acid and phospholipid levels at 1 h. Cell wall biosynthesis was perturbed by sulbactam alone and the combination over 24 h; this was demonstrated by the decreased levels of two important precursors, UDP-N-acetylglucosamine and UDP-N-acetylmuramate, together with perturbed lysine and amino sugar metabolism. Moreover, sulbactam alone and in combination significantly depleted nucleotide metabolism and the associated arginine biosynthesis, glutamate metabolism and pentose phosphate pathway. Notably, the colistin-sulbactam combination decreased amino acid and nucleotide levels more dramatically at 4 h compared to both monotherapies. Conclusions: This is the first metabolomics study revealing the time-dependent synergistic activity of colistin and sulbactam against A. baumannii, which was largely driven by sulbactam through the inhibition of cell wall biosynthesis. Our mechanistic findings may help optimizing synergistic colistin combinations in patients.